MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN METODE DISCOVERY LEARNING PADA MATERI LINGKARAN KELAS XI SMAN 1 PROBOLINGGO - SULAIMAN RASYID (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
The discovery learning method is a teaching method that focuses on the activities of students in learning. This method is used as an alternative to develop students' creative thinking. The 2013 curriculum expects students to be able to think critically to improve learning outcomes. In realizing these expectations, three learning methods can be used in schools, namely (1) Discovery learning, (2) Problem Based Learning, and (3) Project Based Learning. This study aims to describe the implementation of learning mathematics through discovery learning methods that are valid, practical and effective. Meanwhile, according to (Bruner 1996) discovery is a process, a way / way of approaching a problem, not a product or a particular item of knowledge. In the discovery learning method, a verification phase is carried out, which aims that the learning process can run well if the teacher provides opportunities for students to find a concept, theory, rule or understanding through examples that he encounters in his life. The learning outcomes that have been validated are tested through field trials. In this trial, effectiveness was measured based on three indicators, namely (a) learning outcomes test (THB), (b) mathematical reasoning, and (c) the average percentage of student activity observations achieved. Based on the results obtained, the data obtained that the results of the THB number of students who have completed are 91.7%. Based on the established criteria, the results of this test are said to be classically complete. The effectiveness of learning design is also shown by students through activities (1) focusing questions, (2) analyzing questions, (3) delivering answers, (4) giving lots of ideas to a problem, (5) curiosity is quite large, (6) having alternatives in solving problems, (7) proving answers, (8) being active in doing assignments, (9) drawing conclusions. Overall the percentage of implementation of mathematical reasoning is 81.13%, which means it has good criteria. Meanwhile, based on the observation, the average percentage of student activity was 93.79%. So that the overall learning design is considered to have met the specified criteria. ABSTRAKMetode discovery learning adalah metode mengajar yang menitikberatkan pada aktivitas peserta didik dalam belajar. Metode ini digunakan sebagai alternatif untuk mengembangkan berpikir kreatif siswa. Kurikulum 2013 mengharapkan peserta didik mampu berpikir kritis untuk meningkatkan hasil belajar. Dalam mewujudkan harapan tersebut dapat digunakan tiga metode pembelajaran di sekolah yaitu (1) Discovery learning, (2) Problem Based Learning, dan (3) Project Based Learning. Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan pembelajaran matematika melalui metode discovery learning yang valid, praktis dan efektif. Sedangkan menurut (Bruner 1996) penemuan adalah suatu proses, suatu jalan/cara dalam mendekati permasalahan, bukannya suatu produk atau item pengetahuan tertentu. Pada metode discovery learning dilakukan fase verifikasi, yang bertujuan agar proses belajar dapat berjalan dengan baik jika guru memberikan kesempatan kepada peserta didik untuk menemukan suatu konsep, teori, aturan atau pemahaman melalui contoh-contoh yang ia jumpai dalam kehidupannya. Hasil belajar yang telah divalidasi diuji melalui uji coba lapangan. Pada uji coba ini keefektifan diukur berdasar tiga indikator, yaitu (a) tes hasil belajar (THB), (b) penalaran matematika, dan (c) persentase rata-rata ketercapaian observasi aktivitas siswa. Berdasarkan hasil yang dilakukan diperoleh data bahwa hasil THB jumlah siswa yang telah tuntas sebesar 91,7%. Berdasarkan kriteria yang ditetapkan maka hasil tes ini dikatakan tuntas secara klasikal. Keefektifan desain pembelajaran juga ditunjukkan siswa melalui aktivitas (1) memfokuskan pertanyaan, (2) menganalisis pertanyaan, (3)menyampaikan jawaban, (4) memberi banyak gagasan terhadap suatu masalah, (5)Rasa ingin tahu yang cukup besar, (6) memiliki alternatif dalam menyelesaikan masalah, (7) membuktikan jawaban, (8) aktif dalam mengerjakan tugas, (9) menarik kesimpulan. Secara keseluruhan persentase keterlaksanaan penalaran matematika adalah 81,13%, yang berarti mempunyai kriteria baik. Sedangkan berdasarkan observasi persentase rata-rata aktivitas siswa rata-rata ketercapaiannya 93,79%. Sehingga keseluruhan desain pembelajaran dianggap telah mememuhi kriteria yang ditetapkan.